Feeding behavior and performance of Nasonovia ribisnigri on grafts, detached leaves, and leaf disks of resistant and susceptible lettuce. Issue 1 (17th March 2016) - ten Broeke, Cindy J.M.; Dicke, Marcel; van Loon, Joop J.A.
Abstract: Aphids are dependent on the phloem sap of plants as their only source of nutrients. Host‐plant resistance in lettuce, Lactuca sativa L. (Asteraceae), mediated by the Nr gene is used to control the lettuce aphid Nasonovia ribisnigri (Mosely) (Hemiptera: Aphididae). The resistance is located in the phloem; however, the exact mechanism of resistance is unknown. In this study, we investigated whether the resistance factor (or factors) is synthesized in the root or in the shoot. The feeding behavior and performance of avirulent N. ribisnigri were studied on grafts of resistant and susceptible lettuce. In addition, the persistence of resistance in excised lettuce tissue was measured, by studying the feeding behavior and performance of N. ribisnigri on detached leaves and leaf disks of resistant lettuce. It appears that the resistance factor encoded by the Nr gene is produced in the shoots: aphid feeding was reduced on resistant shoots grafted on susceptible roots, whereas aphids were able to feed on grafts of susceptible shoots on resistant roots. Partial loss of resistance was observed after detachment of leaves and excision of leaf disks from resistant plants. Aphids fed longer on excised resistant plant tissue compared with intact resistant plants; however, compared with excised plant tissue of the susceptible cultivar, the time spent on feeding was shorter, indicating resistance was not completely lost. Our findings caution against the use of excised leaf material for aphid resistance bioassays.